Strong typing of object-oriented languages revisited - Madsen, Ole Lehrmann; Magnusson, Boris; Møller-Pedersen, Birger (DAIMI Report Series, 1990)
This paper is concerned with the relation between subtyping and subclassing and their influence on programming language design. Traditionally subclassing as introduced by Simula has also been used for defining a hierarchical type system. The type system of a language can be characterized as strong or weak and the type checking mechanism as static or dynamic. Parameterized classes in combination with a hierarchical type-system is an example of a language construct that is known to create complicated type checking situations. In this paper these situations are analyzed and several different solutions are found. It is argued that an approach with a combination of static and dynamic type checking gives a reasonable balance also here. It is also concluded that this approach makes it possible to base the type system on the class/subclass mechanism.